2007
DOI: 10.1002/jcb.21214
|View full text |Cite
|
Sign up to set email alerts
|

The role of tumor microenvironment in prostate cancer bone metastasis

Abstract: Prostate cancer (PCa) epithelial cells require a number of factors to facilitate their establishment and growth at a distant site of metastasis. Their ability to adapt to their microenvironment, proliferate and recruit an underlying stroma is integral to the survival and growth of the metastasis. PCa predominantly metastasizes to the bone, and bone metastases are the main cause of morbidity. The bone marrow provides a permissive environment for the formation of a metastasis. In some cases, the cells may remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 86 publications
1
73
0
Order By: Relevance
“…Conversely, patients with negative bone marrow aspirate may have cancer cells attached to the endosteal surface that later may develop into metastasis. This may explain in part the lack of correlation between positive aspirates and prognosis in some studies (16,17). Results of this study are consistent with this theory.…”
Section: Discussionsupporting
confidence: 79%
“…Conversely, patients with negative bone marrow aspirate may have cancer cells attached to the endosteal surface that later may develop into metastasis. This may explain in part the lack of correlation between positive aspirates and prognosis in some studies (16,17). Results of this study are consistent with this theory.…”
Section: Discussionsupporting
confidence: 79%
“…Numerous gene expression profiling analyses have allowed researchers to identify specific molecular signatures that may be associated with a high potential of PC cells detected at primary tumors to undergo metastatic spread and establish their homing at specific distant tissues as well as the molecular changes that may occur at the predestinated metastatic sites (23,153,154). In particular, a loss of PTEN, p53 and breast cancer type 1 (BRCA1) combined with an upregulation of EGFR, hedgehog, TGF-β/TGF-βR receptor, ECM components/integrins and SDF-1/ CXCR4 and downstream effectors such as PI3K/Akt, small GTPase Rac-1, mitogenactivated protein kinases, NF-κB, MIC-1 and Rho are often detected in metastatic PC cells (11,135,153,(155)(156)(157)(158)(159)(160)(161)(162)(163)(164)(165)(166). It has also been shown that the migration and engraftment of metastatic PC cells in bones, the most common site of PC metastasis, as well as other distant tissues may be mediated in part through the formation of chemoattractant gradients such as SDF-1 released by host endothelial cells and fibroblasts at distant tissues that specifically attract the metastatic PC cells overexpressing CXCR4 (Figure 1) (23,122,(167)(168)(169).…”
Section: Frequent Gene Products and Molecular Pathways Altered In Metmentioning
confidence: 99%
“…This therapy initially reduces symptoms and metastases growth, but after some time, the metastases relapse to castration-resistant growth (Denmeade & Isaacs 2002). The mechanisms regulating growth of PC bone metastases as well as the mechanisms behind the early treatment response and the later relapse in androgen ablated patients are not fully established (Chen et al 2004, Morrissey & Vessella 2007, Wikstrom et al 2009, Bonkhoff & Berges 2010. Notably, most of our current knowledge about PC is based on studies of primary tumours or soft tissue metastases, and not on studies of bone metastases.…”
Section: Introductionmentioning
confidence: 99%